Peningkatan Aktivitas dan Hasil Belajar Pendidikan Seni Rupa Melalui Penerapan Model Pembelajaran Kontekstual Pada Siswa SMP - Parmada, Ketut (Journal of Education Action Reseach, 2018)
This study aims to (1) improve student learning activities, (2) improve the learning outcomes of students 'visual practices, and (3) describe students' responses to the contextual learning model in Fine Arts education lessons. The research subjects were students of class VIIA2 SMP Negeri 3 Sawan totaling 27 people. The CAR research was conducted in two cycles. The results showed that there was an increase in students' learning activities in learning art education. In the first cycle and second cycle, the average student learning activities were 2.98 (active enough category) and 3.28 (active type). The learning activities of students experienced quality improvement from the first cycle, the average student learning activity was 2.99 (quite active), and cycle II was the average student learning activity of 3.27 (active). Student learning activities from cycle I to cycle II increased by 0.28%. From the results of learning the practice of fine arts in the first cycle obtained the average class, classical absorption and mastery teaching classically in a row: 70.56, 70.56% and 77.78%. Student responses to the contextual learning model are obtained from the average response class of 45.75. Based on the results of this study, the application of contextual learning models can be used as an alternative to increasing student learning activities and outcomes.